Is it possible to use legal defenses to exempt criminal responsibility for the crime of torture? - Bassino Balta, Ariana (2015)
Torture is proscribed in the majority of countries, and prohibited by numerous international instruments. However, torture is nowadays a practice that takes place in many countries, even though there exists a majority agreement in favor of absolute prohibition of this conduct.In the present article, the author analyzes the possibility of using legal defenses to exempt criminal responsibility for the crime of torture. In order to do this, the author examines historical, doctrinal and jurisprudential aspects, concluding than in certain situations it is possible to appeal to traditional legal defenses, particularly selfdefense.